The Level of Participation of Fisherman in the Activities of the Indonesian Fisherman Association (HNSI) in Tanah Merah Village Tanah Merah District Indragiri Hilir Regency, Riau - Ningsih, Ade Widya; Kusai, Kusai; Bathara, lamun (Fakultas Perikanan dan Kelautan Universitas Riau, 2022)
This research aimed to obtain the level of participation of fishermen in the activities of the Indonesian Fishermen Association (HNSI) and to analyze the relationship between internal and external factors on the level of participation of fishermen in the activities of the Indonesian Fishermen Association. This research was conducted in Tanah Merah Village, Tanah Merah District, Indragiri Hilir Regency, Riau Province because there is an organization of the Indonesian Fishermen Association for the Tanah Merah Branch. The method used in this research is a survey method with 37 respondents. Data analysis used descriptive statistics and The Spearman Rank correlation test. The results showed that: (1) The level of participation of fishermen is in the medium category. (2) Spearman Rank correlation test shows that internal and external factors that are significantly related to the level of fisherman participation are income level, the intensity of counseling, benefits or functions, Non-Governmental Organizations (NGOs), and government involvement, while age, education level, number of family dependents, length of stay, and non-member activities are not significantly related.